Successful Treatment of Mycobacterium gordonae Sacroiliitis Using a Novel Minimally Invasive Sacroiliac Joint Arthrodesis: A Case Report. Issue 3 (July 2016) - Wanderman, Nathan; Thurn, Joseph; Wyffels, Mitchell; Sembrano, Jonathan N.
Abstract : Case: A 43-year-old man with a history of well-controlled HIV (human immunodeficiency virus) infection presented with sacroiliac joint destruction from a Mycobacterium gordonae infection. A sacroiliac joint arthrodesis was performed using a minimally invasive technique utilizing both biologic fusion (allograft bone with rhBMP-2 [recombinant human bone morphogenetic protein-2]) and fixation with titanium ingrowth rods. Conclusion: To our knowledge, this is the first reported case of infectious sacroiliitis from a nontubercular mycobacterium (M. gordonae) treated with a combination of joint debridement, biologic fusion with bone graft, and nonbiologic functional fusion using titanium ingrowth rods, all performed in a minimally invasive fashion. This strategy effectively alleviated pain and preserved function at 2 years of follow-up.